Intra-arterial thrombolysis in acute ischaemic stroke: experience with a superselective catheter embedded in the clot. Issue 6 (June 1996) - Casto, L; Caverni, L; Camerlingo, M; Censori, B; Moschini, L; Servalli, M C; Partziguian, T; Belloni, G; Mamoli, A
Abstract : OBJECTIVES--To report experience of intra-arterial thrombolysis for acute stroke, performed with a microcatheter navigated into the intracranial circulation to impale the clot. METHODS--Patients were selected on the following criteria: (1) clinical examination suggesting a large vessel occlusion in stroke patients between 18 and 75 years; (2) no radiographic signs of large actual ischaemia on CT at admission; (3) angiographically documented occlusion of the middle cerebral artery (MCA) stem or of the basilar artery (BA), without occlusion of the ipsilateral extracranial internal carotid artery or of both the vertebral arteries; (4) end of the entire procedure within six hours of stroke. 12 patients with acute stroke were recruited, eight of whom had occlusion of the MCA stem and four of the BA. Urokinase was used as the thrombolytic agent. RESULTS--Complete recanalisation in six MCA stem and in two BA occurred, and partial recanalisation in two MCA stem and one BA. There was no recanalisation in one BA. A clinically silent haemorrhage occurred in two patients, and a parenchymal haematoma in one patient, all in MCA occlusions. At four months five patients achieved self sufficiency (four with MCA and one with BA occlusion). Six patients were dependent (three totally), and one died. CONCLUSIONS--The strict criteria of eligibility allowing the enrollment of very few patients and the procedure itself, requiring particular neuroradiological expertise, make this procedure not routine. Nevertheless, the approach can be considered a possible option for patients with acute ischaemic stroke.